2017
DOI: 10.1002/eap.1466
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of trophic hotspots and relation to human impacts within an upwelling marine ecosystem

Abstract: Human impacts (e.g., fishing, pollution, and shipping) on pelagic ecosystems are increasing, causing concerns about stresses on marine food webs. Maintaining predator-prey relationships through protection of pelagic hotspots is crucial for conservation and management of living marine resources. Biotic components of pelagic, plankton-based, ecosystems exhibit high variability in abundance in time and space (i.e., extreme patchiness), requiring investigation of persistence of abundance across trophic levels to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 80 publications
(204 reference statements)
3
44
0
1
Order By: Relevance
“…For seven of the eight species considered in this study, the best predictive models developed using 1991-2009 survey data successfully captured shifts in distribution and change in absolute abundance during an anomalously warm year. The average 2014 SST value was substantially higher than in 1991-2009 (Table 3), consistent with multiple studies that revealed dramatic changes in SST and other oceanic properties in 2014 (Bond et al, 2015;Cavole et al, 2016;Leising et al, 2015 (Rykaczewski et al, 2015), and there could be shifts in the locations of such hotspots (Santora et al, 2017) and consequently the foraging grounds for blue and humpback whales.…”
Section: Did the Models Accurately Predict Changes In Species Abundsupporting
confidence: 86%
See 2 more Smart Citations
“…For seven of the eight species considered in this study, the best predictive models developed using 1991-2009 survey data successfully captured shifts in distribution and change in absolute abundance during an anomalously warm year. The average 2014 SST value was substantially higher than in 1991-2009 (Table 3), consistent with multiple studies that revealed dramatic changes in SST and other oceanic properties in 2014 (Bond et al, 2015;Cavole et al, 2016;Leising et al, 2015 (Rykaczewski et al, 2015), and there could be shifts in the locations of such hotspots (Santora et al, 2017) and consequently the foraging grounds for blue and humpback whales.…”
Section: Did the Models Accurately Predict Changes In Species Abundsupporting
confidence: 86%
“…These predictions are consistent with abundance estimates derived from the 2014 survey data that indicate a decrease in blue whale abundance in the study area as compared to the 1996-2009 average, and a more than doubling of estimated humpback whale abundance in 2014 (Table 2; Barlow, 2016). Blue and humpback whales were the only species for which Model 3 made the best novel predictions, consistent with observations that these large migrators return to the same largely coastal foraging grounds every season, perhaps due to learned behaviour and/or the persistence of trophic hotspots (Baker et al, 2013;Barlow, Calambokidis, et al, 2011;Calambokidis et al, 2008Calambokidis et al, , 2015Irvine et al, 2014;Santora et al, 2017).…”
Section: Model Comparison: Predictive Performancesupporting
confidence: 75%
See 1 more Smart Citation
“…Santora et al . [, ] also found significant coupling between physics, primary production, micronekton (including krill), and top predators off central and southern California.…”
Section: Introductionmentioning
confidence: 99%
“…High prey concentrations increase predator survival [Pitchford and Brindley, 2001], and patchiness is a key characteristic of oceanic ecosystems. The term "hotspot" has been used in the literature to describe areas of high prey and predator abundance that form at scales ranging from meters to hundreds of kilometers [e.g., Hazen et al, 2013;Bertrand et al, 2014;Santora et al, 2017]. Of particular interest are hotspots of large (meso/macro) zooplankton such as copepods and krill that are a primary food source for fish and marine mammals including sardines, anchovies, and whales [Van Der Lingen, 2002;Espinoza et al, 2009;Croll et al, 2005].…”
Section: Introductionmentioning
confidence: 99%